The Female Gaze in Carol Ann Duffy’s The World’s Wife - et. al., Sangeetha J, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The World’s Wife (1999) penned by Carol Ann Duffy; it is a collection of poems. Which discusses about marital rape, child abuse, domestic violence, verbal abuse, marginalizing of a particular sex, body shaming and the gaze are some of the major reasons why Duffy had to write this poem. There are many misconceptions about Feminism and its theories. The researcher has planned to give a clear view about feminism. By applying the concept of Female Gaze. This poetry is very unique because various characters in the poem has been extracted from Greek Mythology, adapted from various films, fairy tales and narrated from the counter parts of famous writers. The poet has chosen simple words and used it in a complicated way. This world is still a horrible place for a woman to live her own life. This work is so important because the poet herself depicts the entire woman society